Respuesta :
After multiplying by the stated coefficients and adding, the equation obtained is:
8y - 7.5y = 0
y = 0
x = 4
Because the two equations formed were independent, they had one solution.
8y - 7.5y = 0
y = 0
x = 4
Because the two equations formed were independent, they had one solution.
the answer
9x + 4y = 36 (times 2) implies 18x + 8y = 72 (a)
6x + 2.5y = 24 (times -3) imiplies 18x + 7.5y =72 (b)
so (a) - (b) 8-7.5)y=0, and y=0
when y=o 18x + 8. 0= 72 implies x =4
so the solution is (4,0)
9x + 4y = 36 (times 2) implies 18x + 8y = 72 (a)
6x + 2.5y = 24 (times -3) imiplies 18x + 7.5y =72 (b)
so (a) - (b) 8-7.5)y=0, and y=0
when y=o 18x + 8. 0= 72 implies x =4
so the solution is (4,0)